CHANGING FOREIGN LANGUAGE TEACHING STANDARDS AS A CONDITION FOR UNIVERSITY GRADUATES’ EMPLOYABILITY - Vorontsova, Marina; Klyukina, Evgeniya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The main aim of the study is to substantiate a new foreign language teaching standard in the universities of Russia closing the gap between the standards and the modern job market demands. In order to achieve this aim it is necessary to define the vector of the changes and correlate them with the bachelor and master students’ requirements. The main changes which the modern labor market is undergoing are the emergence of new related professions, blurring borders between professions, difficulties defining narrow vocational standards. The study hypothesizes that foreign language teaching standards should be transformed towards greater interdisciplinarity and development of soft skills rather than a merely linguistic component in the course. The main methods of research, namely analyzing literature on the soft skills in demand with employers, polls of bachelors and masters on the need and possibility to develop soft skills in the ELT classroom, allowed identifying the soft skills which are in greater demand in terms of employability in the modern job market and received a positive feedback from the respondents – communicative competence, learnability, critical and creative thinking, collaboration skills. A similar poll was conducted among the graduates of the CAAS MSU working in various spheres. The study resulted in developing the new foreign language teaching standard which encompasses teaching two European languages, instructing with the help of interdisciplinary materials and forming soft skills on all the stages of foreign language acquisition.